(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical, paraclinical characteristics, and evaluate the outcomes of laparoscopic surgery for cesarean scar defects. Subjects and Methods: This is a cross-sectional descriptive study with prospective data collection on 21 patients who underwent laparoscopic surgery for cesarean scar defects at the Reproductive Support Center – Nghệ An Friendship General Hospital from June 2022 to June 2023. The study investigated the clinical and paraclinical symptoms of the patients before and after surgery. Results: The average age of the patients was 34.48 ± 4.75 years, with 41.6% having been infertile for over 5 years. Symptoms before surgery included post-menstrual bleeding in 90.4%, mid-cycle bleeding in 19%, dysmenorrhea in 33.3%, and pelvic pain in 23.8%. After surgery, post-menstrual bleeding decreased to 19%, mid-cycle bleeding disappeared, dysmenorrhea reduced to 14.3%, and pelvic pain decreased to 9.5%. Before surgery, 100% of patients had a cesarean scar defect and uterine cavity fluid, with 52.4% having a retroverted uterus. 76.2% had a triangular-shaped defect, 61.9% had a type III defect, and the remaining myometrial thickness was 2.79±1.17mm. After surgery, 47.6% of patients still had a scar defect, 14.3% had uterine cavity fluid, 19% had a retroverted uterus, 38.1% had a triangular-shaped defect, 9.5% had a type III defect, and the remaining myometrial thickness was 5.07±1.29mm. There was a correlation between the degree of scar defect and menorrhagia symptoms (p<0.05). Conclusion: Patients with cesarean scar defects had an over 90% rate of abnormal menstruation. The defects were mainly found in retroverted uteri with a triangular defect shape. The size of the defect was related to the severity of clinical symptoms. Laparoscopic surgery for cesarean scar defects significantly improves clinical and paraclinical symptoms, has few complications.